Novel Cross Screw with Staple for First MTP Joint Arthrodesis Compared to Dorsal Plate Fixation: Retrospective Clinical and Radiographic Evaluation - Stephen R. Arndt MD; Shirin Zahra BS; Mark Moldavsky MS (Foot & Ankle Orthopaedics)
Category: Lesser Toes; Other Introduction/Purpose: Retrospective study investigating patient reported outcomes and radiographic evaluation of crossed screws used in conjunction with a compressive nitinol staple (CS+S) for arthrodesis of the 1st metatarsophalangeal (MTP) joint. Dorsal plating (DP) group for 1st MTP joint was used for as control group. Methods: Pre-op and post-op Visual Analog Score (VAS) were assessed. Radiographic Hallux Valgus Angle (HVA), Intermetatarsal Angle (IMA), Interphalangeal Angle (IPA) Dorsiflexion Angle (DFA), and distance of fibular sesamoid (DFS) were measured pre-op and post-op. Student t-test assuming equal variance (p≤0.05) was performed to determine significance. Fusion was determined by assessing post operative radiographs. Results: DP Group had 40 patients, age 65.3±8.4, 12M, 28F, BMI 30.4±6.2. In the CS+S group 14 patients were included age 66.64±8.4, 5M, 9F, BMI 25.0±3.8. DP had a average follow up time of 4±3months with 95% fusion rate; CS+S had 100% fusion rate at an average follow up of 1.9±2months. Pre-op and Post-op DP and CS+S VAS scores were (7.9±0.9; 1.3±1) and (8.0±0.8; 0.7±0.9), respectively (p≤0.05). Pre and post-op HVA, IMA, IPA, DFA and DFS for DP are 19.9±11.25o, 8.32±7.19o (p≤0.05); 11.41±4.58o, 9.09±3.23o (p≤0.05); 9.99±4.84o, 12.95±4.12o (p≤0.05); 22.59±9.21o, 23.71±7.41o (p≥0.05); and 12.82±2.65mm, 12.35±2.62mm (p≥0.05) respectively. Pre and post-op HVA, IMA, IPA, DFA angles and DFS for CS+S are 21.71±10.5o, 5.57±5.08o (p≤0.05); 10.54±4.43o, 7.98±2.79o (p≤0.05); 11.99±6.28o, 14.47±5.22o (p≥0.05); 22.26±8.90o, 22.44±8.97o (p≥0.05); and 13.24±2.17mm, 12.13±1.56mm (p≥0.05) respectively. Conclusion: Both Cross Screw + Staple and Dorsal Plate groups result in significant improvements in VAS scores and radiographic parameters. The Cross Screw + Staple group had 100% fusion rate with significantly less follow up time compared to Dorsal Plate Group. Performing the procedure with Cross Screws + Staple has the benefits of a smaller incision, lower profile implant, less hardware irritation while providing continuous compression across the joint. potential benefits may be decreased OR room time and reduced hospital cost.